Troca gasosa pulmonar e desoxigenação muscular e cerebral durante o exercício incremental em homens com diabetes mellitus tipo 2 e saudáveis - Fabricio, Amanda Magdalena Ferroli (2017)
Aims: To investigate factors related to physical exercise intolerance in T2D comparing similarities and differences between type 2 diabetes (T2D) and healthy adjustments of cardiorespiratory system and cerebral and peripheral muscle oxygentation during an incremental cardiopulmonary exercise test (CPET).Methods:Twenty-two men with T2D (T2DG) and 18 apparently healthy controls (CG) performed incremental cycling exercises. Pulmonary oxygen uptake, cerebral and muscle oxygenation were measured using a computerized metabolic cart, a near-infrared spectrophotometer (NIRS), system, respectively. Results:The groups were similar for age (CG: 53.6 ± 3.8 vsT2DMG: 54.9 ± 5.6) and body mass index (BMI) (CG: 27.8 ± 2.4 vsT2DMG: 27.51.9). T2DMG presented lower aerobic capacity (VO2peak: 20.0 ± 4.2 vs23.2 ± 4.7) and workload (134.5 ± 27.5 vs158.8 ± 35.7) compared to CG. Cerebral [HHb] presentedan inverse responsebetween groups, CG increased during exercise, while T2DG reduced. The [HHb] responseof the VL was similar between the groups.Conclusions:Individuals with T2D presented reducedcardiopulmonary performance and abnormalbehavior of cerebral deoxygenation(compared with health). The data suggest that microvascular changes can affect tissues with a high sensitivity to oxygen depletion, such as the brain region, affecting cerebral auto-regulation which could be related with reduced exercise tolerance in diabetic patients.